2022
DOI: 10.1039/d2py00405d
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic selective coupling of episulfides with carbon disulfide for the synthesis of poly(trithiocarbonate)s and cyclic trithiocarbonates

Abstract: Selective coupling of CS2 with episulfides affords perfectly alternating poly(trithiocarbonate)s or cyclic trithiocarbonates upon the onium salts used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…The DTCM polymer, which seamed the gel networks of the pAAm gels, had cyclic trithiocarbonate substitutes. Cyclic trithiocarbonate molecules have high reactivity, as previously reported by others. , They were used to change the chemical structures and adhesive gel joints.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The DTCM polymer, which seamed the gel networks of the pAAm gels, had cyclic trithiocarbonate substitutes. Cyclic trithiocarbonate molecules have high reactivity, as previously reported by others. , They were used to change the chemical structures and adhesive gel joints.…”
Section: Resultsmentioning
confidence: 76%
“…Cyclic trithiocarbonate molecules have high reactivity, as previously reported by others. 38,39 They were used to change the chemical structures and adhesive gel joints.…”
Section: Reaction Of the Adhesive Joint With Aminesmentioning
confidence: 99%
“…Nevertheless, the corresponding polymers can be obtained by other means, as has been demonstrated by Gnanou/Feng and co-workers. 120 In this work, the obtained polymers also underwent complete unzipping when treated with radicals or under UV light irradiation to form the cyclic trithiocarbonates. This unexpected activity was exploited to prepare degradable polymers using oligotrithiocarbonates as self-immolating linkers between dithiol alkyl precursors.…”
Section: Reviewmentioning
confidence: 88%
“…28c). 120 In this metal-free process, the cyclic trithiocarbonates can be selectively obtained by reaction of the thiirane and carbon disulfide using tetrabutylammonium fluoride (TBAF) at 80 °C. It was indicated that above 60 °C when using fluoride as nucleophile, back-biting reactions largely predominate over propagation, resulting in the formation of the cyclic product.…”
Section: Cyclic Trithiocarbonatesmentioning
confidence: 99%
“…33 To our knowledge, few CS 2 -based polymerizations have been reported except CS 2 /diamine polymerization, 19 CS 2 /epoxide copolymerization, 28 and CS 2 /episulfide copolymerization. 29 Moreover, Endo and other groups have reported the polyaddition between diamines and bifunctional five-membered cyclic dithiocarbonates, which are synthesized from the reaction between CS 2 and diepoxides. 30,34,35 Herein, we report a new MCP of diamines, CS 2 , and diepoxides to produce functional polydithiourethanes with various molecular structures.…”
Section: Introductionmentioning
confidence: 99%